Socio-spatial influences on the teaching-learning process in early childhood education: a case study from the perspective of spatial syntax - Baracho, Alberlene; Fernandes, Marciele da Silva; Gomes, Larissa Baracho; Machado, Marcia de Oliveira Silva (Brazilian Journal of Production Engineering, 2025)
This brief essay aims to perform an analysis of spatial syntax in a school environment. From the perspectives of Piaget and Vygotsky, we seek to understand possible influences of layout in the teaching-learning process. Through spatial syntax, it is possible to evaluate the integration and connection of spaces, understanding the potentialities and weaknesses of the usability of buildings. Therefore, present the points that can favor the development of socio-emotional and cognitive aspects through the experience with the lived space. In an early childhood education school, understanding the use of space favors experiences and continuous learning, enabling the right to healthy development at all stages of childhood.